Hadith #2117 - Sunan Abi Dawud - Abu 'Ubaidah ibn al-Jarrah; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Mas'ud; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said to a man: Would you like me to marry you to so-and-so? He said: Yes. He also said to the woman: Would you like me to marry you to so-and-so? She said: Yes. He then married one to the other. The man had sexual intercourse with her, but he did not fix any dower for her, nor did he give anything to her. He was one of those who participated in the expedition to al-Hudaybiyyah. One part of the expedition to al-Hudaybiyyah had a share in Khaybar. When he was nearing his death, h
Grade: Sahih

Hadith #2147 - Sunan Abi Dawud - Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Amr bin Sa'id bin al-As عمرو بن سعيد بن العاص- الأشدق; Jarir bin 'Abdullah al-Bajli; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yonus bin 'Ubaid bin Dinar يونس بن عبيد بن دينار العبدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man will not be asked as to why he beat his wife.
Grade: Hasan

Hadith #2200 - Sunan Abi Dawud - Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar ibn al-Khattab; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
Abu al-Sahba’ said to Ibn Abbas: Do you know that a divorce by three pronouncements was made a single one during the time of the Prophet (ﷺ), and of AbuBakr and in the early days of the caliphate of Umar? He replied: Yes.
Grade: Sahih

Hadith #2287 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Fatima bint Qays; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Fatimah daughter of Qais said “I was married to a man of Banu Makhzum. He divorced me absolutely. The narrator then transmitted the rest of the tradition like that of Malik. This version has “Do not marry yourself without my permission.” Abu Dawud said Al Sha’bi, Al Bahiyy and ata from abd Al Rahman bin asim and Abu Bakr bin Abi Al Jahm all narrated on the authority of Fatimah daughter of Qais that her husband had divorced her three times.
Grade: Sahih

Hadith #2292 - Sunan Abi Dawud - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
Aisha (Allah be pleased with her) severely objected to the tradition of Fatimah daughter of Qays. She said: Fatimah lived in a desolate house and she feared for her loneliness there. Hence the Messenger of Allah (ﷺ) accorded permission to her (to leave the place).
Grade: Hasan

Hadith #2309 - Sunan Abi Dawud - Amr bin Sharhbayl, Abu Maysara عمرو بن شرحبيل الهمداني أبو ميسرة الكوفي; ibn Mas'ud; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about a man who divorced his wife three times, and she married another who entered upon her, but divorced her before having intercourse with her, whether she was lawful for the former husband. She said: The Prophet (ﷺ) replied: She is not lawful for the first (husband) until she tastes the honey of the other husband and he tastes her honey.
Grade: Sahih

Hadith #2375 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
We would not allow a man who was fasting to get himself cupped due to abomination of hardship.
Grade: Sahih

Hadith #2383 - Sunan Abi Dawud - Aisha bint Abi Bakr; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) used to kiss (me) during the month of fasting.
Grade: Sahih

Hadith #2395 - Sunan Abi Dawud - Abu al-Matwas أبو المطوس; Abu Hurairah; Amarh bin 'Umayr al-Tymy عمارة بن عمير التيمي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A huge basket containing twenty sa’s (of dates) was brought.
Grade: Hasan

Hadith #2400 - Sunan Abi Dawud - ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If anyone dies when some fast is due from him (i.e. which he could not keep) his heir must fast on his behalf. Abu Dawud said: This applies to the fast which a man vows ; and this is the opinion of Ahmad b. Hanbal.
Grade: Sahih

Hadith #2421 - Sunan Abi Dawud - Abu Ayyub al-Ansari; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Juwayriya bint al-Harith; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not fast on Saturday except what has been made obligatory on you; and if one of you can get nothing but a grape skin or a piece of wood from a tree, he should chew it.
Grade: Sahih

Hadith #2448 - Sunan Abi Dawud - Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: The fast most liked by Allah is the one observed by Dawud (David), and the prayer dearer to Allah is the one offered by Dawud (David): he would sleep half the night, and stand (in prayer) one-third of it, and sleep one-sixth of it. He would go without fasting one day, and fast the other day.
Grade: Sahih

Hadith #2454 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who does not determine to fast before dawn does not fast.
Grade: Sahih

Hadith #2523 - Sunan Abi Dawud - Abdullah bin Rabi'a bin Farqad عبد الله بن ربيعة بن فرقد السلمي; Amr bin Maymun al-Aw'di عمرو بن ميمون الأودي أبو عبد الله; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaid bin Khalid al-Slmy (Sunan Abi Dawud)
When Negus died, we were told that a light would be seen perpetually at his grave.
Grade: Hasan

Hadith #2527 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) announced an expedition, and I was a very old man and I had no servant. I, therefore, sought a hireling who would serve instead of me, and I would give him his portion. So I found a man. When the time of departure arrived, he came to me and said: I do not know what would be the portions, and how much would be my portion. So offer something (as wages) to me, whether there would be any portion or not. I offered three dinars (as his wages) for him. When some booty arriv
Grade: Sahih

Hadith #2528 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Farroukh, Abu al-Abbas السائب بن فروخ أبو العباس الشاعر; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man came to the Messenger of Allah (ﷺ) and said: I came to you to take the oath of allegiance to you on emigration, and I left my parents weeping. He (the Prophet) said: Return to them and make them laugh as you made them weep.
Grade: Sahih

Hadith #2546 - Sunan Abi Dawud - Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to name a mare a horse.
Grade: Sahih

Hadith #2563 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Anas bin Malik said “I brought my brother when he was born to Prophet(ﷺ) to chew something for him and rub his palate with it and found him in a sheep pen branding the sheep, I think, on their ears.”
Grade: Sahih

Hadith #2596 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Ilyas bin Salamah(bin Al Akwa’) said on the authority of his father “We went on an expedition with Abu Bakr (Allaah be pleased with him) in the time of the Apostle of Allaah(ﷺ) and our war cry was “Put to death” “Put to death”.”
Grade: Sahih

Hadith #2747 - Sunan Abi Dawud - Habib bin Muslama; Makhul al-Shami/al-Damashiqi مكحول الشامي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ziyad bin Jariyya bin al-Tamimi زياد بن جارية التميمي الدمشقي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out on the day of Badr along with three hundred and fifteen (men). The Messenger of Allah (ﷺ) said: O Allah, they are on foot, provide mount for them; O Allah , they are naked, clothe them; O Allah, they are hungry, provide food for them. Allah then bestowed victory on them. They returned when they were clothed. There was no man of them but he returned with one or two camels; they were clothed and ate to their fill.
Grade: Hasan

Hadith #2761 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Harithh bin Mdrb حارثة بن مضرب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say when they (messengers sent by Musaylimah) read the letter of Musaylimah: What do you believe yourselves? They said: We believe as he believes. He said: I swear by Allah that were it not that messengers are not killed, I would cut off your heads.
Grade: Sahih

Hadith #2817 - Sunan Abi Dawud - Ikrama عكرمة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan Abi Dawud)
The verse: “So eat of (meats) on which Allah’s name hath been pronounced” and the verse: “Eat not of (meats) on which Allah’s name hath not been pronounced” were abrogated, meaning an exception was made therein by the verse: “The food of the people of the Book is lawful unto you and yours is lawful unto them.”
Grade: Hasan

Hadith #2853 - Sunan Abi Dawud - Abdullah bin Abi al-Safar عبد الله بن أبي السفر; Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
Messenger of Allah, one of us shoots at the game, and follows its mark for two or three days, and then finds it dead, and there is his arrow (pierced) in it, may he eat it? He said: Yes, if he wishes, or he said: he may eat if he wishes.
Grade: Sahih

Hadith #2875 - Sunan Abi Dawud - Khabbab ibn al-Aratt; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
A man asked him (the Prophet): Messenger of Allah, what are the grave sins? He replied: They are nine. He then mentioned the tradition to the same effect. This version adds: “And disobedience to the Muslim parents, and to violate the sacred House, your qiblah (direction of prayer), in your life and after death.
Grade: Hasan

Hadith #2895 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Imran bin Husain; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) appointed a sixth to a grandmother if no mother is left to inherit before her.
Grade: Hasan

Hadith #2953 - Sunan Abi Dawud - Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When the spoils (fai’) came to the Messenger of Allah (ﷺ), he divided it that day ; he gave two portions to a married man and one to a bachelor. The narrator Ibn al-Musaffa added: We were summoned, and I would be summoned before ‘Ammar. So I was summoned and he gave me two portions, for I had a family ; then ‘Ammar b. Yasir was summoned after me and given one.
Grade: Sahih

Hadith #2990 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Mujja’ah went to the Prophet (ﷺ) asking him for the blood-money of his brother whom Banu Sadus from Banu Dhuhl had killed. The Prophet (ﷺ) said: Had I appointed blood-money for a polytheist, I should have appointed it for your brother. But I shall give you compensation for him. So the Prophet (ﷺ) wrote (a document) for him that he should be given a hundred camels which were to be acquired from the fifth taken from the polytheists of Banu Dhuhl. So he took a part of them, for Banu Dhuhl e
Grade: Da'if

Hadith #3053 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Jizyah is not to be levied on a Muslim.
Grade: Da'if

Hadith #3097 - Sunan Abi Dawud - Abdullah bin Nafi' al-Sa'agh عبد الله بن نافع الصائغ المخزومي; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone performs ablution well and pays a visit to his (sick) Muslim brother seeking his reward from Allah, he will be removed a distance of seventy years (kharif) from Hell. I asked: What is kharif, Abu Hamzah? He replied: A year. Abu Dawud said: Only the people of Basrah have narrated the tradition on visiting the sick after performing ablution.
Grade: Da'if

Hadith #3114 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Umm Salamah (Sunan Abi Dawud)
When the time of his death came, he called for new clothes and put on them. He then said: I heard the Messenger of Allah (ﷺ) say: A deceased will be raised in the clothes in which he died.
Grade: Sahih

Hadith #3121 - Sunan Abi Dawud - Aisha bint Abi Bakr; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Umarh bint 'Abdur Rahman عمرة بنت عبد الرحمن بن سعد بن زرارة; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Recite Surah Ya-Sin over your dying men. This is the version of Ibn al-Ala’
Grade: Da'if

Hadith #3154 - Sunan Abi Dawud - Khabbab ibn al-Aratt; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
Do not be extravagant in shrouding, for I heard the Messenger of Allah (ﷺ) say: Do not be extravagant in shrouding, for it will be quickly decayed.
Grade: Da'if

Hadith #3162 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
This has been abrogated. When Ahmad b. Hanbal was asked about a man taking a bath after his washing the dead, I heard him say: Ablution is sufficient for him. Abu Dawud said: The narrator Abu Salih made a mention of the narrator Ishaq, the client of Za’idah between him and Abu Hurairah. He said: The tradition of Mus’ab is weak. It contains many things that are not practised.
Grade: Sahih

Hadith #3164 - Sunan Abi Dawud - al-Aswad bin Qays al-Bdy الأسود بن قيس العبدي; Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The people saw fire (light) in the graveyard and they went there. They found that the Messenger of Allah (ﷺ) was in a grave and he was saying: Give me your companion. This was a man who used to raise his voice while mentioning the name of Allah.
Grade: Hasan

Hadith #3197 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin 'Abdullah طلحة بن عبد الله بن عوف الزهري (Sunan Abi Dawud)
Zaid b. Arqam used to utter four takbirs (Allah is Most Great) over our dead person (during prayer). He uttered five takbirs on a dead person. So I asked him. He replied: The Messenger of Allah (ﷺ) used to utter those. Abu Dawud said: I remember the tradition of Ibn al-Muthanna in a more guarded way.
Grade: Sahih

Hadith #3212 - Sunan Abi Dawud - Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
We went out with the Messenger of Allah (ﷺ) to the funeral of a man of the Ansar, but when we reached the grave, the niche in the side had not yet been made, so the Prophet (ﷺ) sat down facing the qiblah, and we sat down along with him.
Grade: Sahih

Hadith #3217 - Sunan Abi Dawud - Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
This tradition has also been transmitted by Sa’d b. Hisham b. ‘Amir with a different chain of narrators.
Grade: Sahih

Hadith #3235 - Sunan Abi Dawud - Abu Salah Maula 'Uthman أبو صالح مولى عثمان; ibn Abbas; Muhammad bin Jahada محمد بن جحادة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: I forbade you to visit graves, but you may now visit them, for in visiting them there is a reminder (of death).
Grade: Sahih

Hadith #3237 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out to the graveyard and said: Peace be upon you, inhabitants of the dwellings who are of the community of the believers. If Allah wills we shall join you.
Grade: Sahih

Hadith #3268 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
Abu Hurairah narrated that a man came to the Messenger of Allah (ﷺ) and said: I had a dream last night, and he then mentioned it. So Abu Bakr interpreted it. The Prophet (ﷺ) said: You are partly right and partly wrong. He then said: I adjure you, Messenger of Allah, may my father be sacrificed on you, do tell me the mistake I have committed. The Prophet (ﷺ) said: Do not adjure.
Grade: Sahih

Hadith #3388 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Rafi' bin Khadij bin Rafi'; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I Ammar, and Sa’d became partners in what we would receive on the day of Badr. Sa’d then brought two prisoners, but I and Ammar did not bring anything.
Grade: Da'if

Hadith #3397 - Sunan Abi Dawud - Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Usayd bin Zuhayr bin Rafi' (Sunan Abi Dawud)
AbuRafi’ came to us from the Messenger of Allah (ﷺ) said: The Messenger of Allah (ﷺ) forbade us from a work which benefited us; but obedience to Allah and His Apostle (ﷺ) is more beneficial to us. He forbade that one of us cultivates land except the one which he owns or the land which a man lends him (to cultivate).
Grade: Sahih

Hadith #3466 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We made a journey to Syria on an expedition along with the Messenger of Allah (ﷺ). The Nabateans of Syria came to us and we paid in advance to them (in a salam contract) in wheat and olive oil at a specified rate and for a specified time. He asked (by the people): you might have contracted with him who had these things in his possession? He replied: We did not ask them.
Grade: Sahih

Hadith #3527 - Sunan Abi Dawud - Aisha bint Abi Bakr; Amarh bin 'Umayr al-Tymy عمارة بن عمير التيمي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
reported the Prophet (ﷺ) as saying: There are people from the servants of Allah who are neither prophets nor martyrs; the prophets and martyrs will envy them on the Day of Resurrection for their rank from Allah, the Most High. They (the people) asked: Tell us, Messenger of Allah, who are they? He replied: They are people who love one another for the spirit of Allah (i.e. the Qur’an), without having any mutual kinship and giving property to one. I swear by Allah, their faces will glow and the
Grade: Sahih

Hadith #3577 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Anas ibn Malik; Bilal ibn Ribah; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
Two men from the locality of Kindah came while AbuMas’ud al-Ansari was sitting n a circle. They said: Is there any man who decides between us. A man from the circle said: I, AbuMas’ud took a handful of pebbles and threw at him, saying: Hush! It is disapproved to make haste in decision.
Grade: Da'if

Hadith #3582 - Sunan Abi Dawud - Hisham bin 'Urwa هشام بن عروة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Salamah; Urwa ibn al-Zubayr عروة بن الزبير; Zaynab bint Abi Salamah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent me to the Yemen as judge, and I asked: Messenger of Allah, are you sending me when I am young and have no knowledge of the duties of a judge? He replied: Allah will guide your heart and keep your tongue true. When two litigants sit in front of you, do not decide till you hear what the other has to say as you heard what the first had to say; for it is best that you should have a clear idea of the best decision. He said: I had been a judge (for long); or he said (
Grade: Hasan

Hadith #3588 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave the decision that the two adversaries should be made to sit in front of the judge.
Grade: Da'if

Hadith #3739 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Nafi’ to the same effect through the chain of narrators as mentioned in Ayyub.
Grade: Sahih

Hadith #3762 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out from the valley of a mountain where he had eased himself. There were some dried dates on a shield before us. We called him and he ate with us. He did not touch water.
Grade: Da'if

Hadith #3768 - Sunan Abi Dawud - Abu Juhayfa al-Sawai'; Ali bin al-Aqmar bin 'Amr علي بن الأقمر بن عمرو; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Umayyah was sitting and a man was eating. He did not mention Allah’s name until there remained the last morsel. When he raised it to his mouth, he said: In the name of Allah at the beginning and at the end of it. The Prophet (ﷺ) laughed and said: The devil kept eating along with him, but when he mentioned Allah’s name, he vomited what was in his belly. Abu Dawud: Jabir bin Subh is grandfather of Sulaiman bin Harb from his mother’s side.
Grade: Hasan

Hadith #3832 - Sunan Abi Dawud - Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Ishaq bin 'Abdullah bin Abi Talha إسحاق بن عبد الله بن أبي طلحة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
When the Prophet (ﷺ) was brought some old dates, he began to examine them and remove the worms from them.
Grade: Sahih

Hadith #3870 - Sunan Abi Dawud - Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited unclean medicine.
Grade: Sahih

Hadith #3909 - Sunan Abi Dawud - ibn Mas'ud; Isa bin 'Asim al-Asady عيسى بن عاصم الأسدي الكوفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan Abi Dawud)
I said: Messenger of Allah! among us there are men who practice divination by drawing lines. He said: There was a Prophet who drew lines, so if anyone does it as he drew lines, that is right.
Grade: Sahih

Hadith #3932 - Sunan Abi Dawud - Abu al-Malih; Hamam bin Munabbih همام بن منبه بن كامل; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
Safinah said: I was a slave of Umm Salamah, and she said: I shall emancipate you, but I stipulate that you must serve the Messenger of Allah (ﷺ) as long as you live. I said: Even if you do not make a stipulation, I shall not leave the Messenger of Allah (ﷺ). She then emancipated me and made the stipulation with me.
Grade: Hasan

Hadith #3933 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
On his father’s authority (this is AbulWalid’s version): A man emancipated a share in a slave and the matter was mentioned to the Prophet (ﷺ). He said: Allah has no partner. Ibn Kathir added in his version: The Prophet (ﷺ) allowed his emancipation.
Grade: Sahih

Hadith #3967 - Sunan Abi Dawud - Abu al-Darda; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
“If a man emancipates two Muslim women, they will be deliverance from Hell fire; two bones of their will be emancipation for each of his bone.” Abu Dawud said: Salim did not hear (traditions) from Shurahbil. Shurahbil died at Siffin.
Grade: Sahih

Hadith #3979 - Sunan Abi Dawud - Aslm al-Mnqry Abu Sa'id Hdythh أسلم المنقري; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubayy ibn Ka'b (Sunan Abi Dawud)
The Prophet (ﷺ) read the verse mentioned above, “min du’f.”
Grade: Hasan

Hadith #4073 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) at Mina giving sermon on a mule and wearing a red garment, while Ali was announcing.
Grade: Sahih

Hadith #4122 - Sunan Abi Dawud - ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Al-Zuhri used to deny tanning and say: Some good can be got out of it in any condition Abu Dawud said: Al-Auza’i, Yunus and ‘Uqail did not mention tanning. al-Zubaidi, Sa’id b. ‘Abd al-Aziz and Hafs b. ‘Abd al-‘Aziz mentioned tanning.
Grade: Da'if

Hadith #4173 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a woman uses perfume and passes the people so that they may get its odour, she is so-and-so, meaning severe remarks.
Grade: Hasan

Hadith #4369 - Sunan Abi Dawud - Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة (Sunan Abi Dawud)
Some people raided the camels of the Prophet (ﷺ), drove them off, and apostatised. They killed the herdsman of the Messenger of Allah (ﷺ) who was a believer. He (the Prophet) sent (people) in pursuit of them and they were caught. He had their hands and feet cut off, and their eyes put out. The verse regarding fighting against Allah and His Prophet (ﷺ) was then revealed. These were the people about whom Anas ibn Malik informed al-Hajjaj when he asked him.
Grade: Hasan Sahih

Hadith #4402 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Atyh al-Qrzy Bdm; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
AbuZubyan said: A woman who had committed adultery was brought to Umar. He gave orders that she should be stoned. Ali passed by just then. He seized her and let her go. Umar was informed of it. He said: Ask Ali to come to me. Ali came to him and said: Commander of the Faithful, you know that the Messenger of Allah (ﷺ) said: There are three (people) whose actions are not recorded: A boy till he reaches puberty, a sleeper till he awakes, a lunatic till he is restored to reason. This is an idiot
Grade: Sahih

Hadith #4471 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Ali ibn Abi Talib; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
He said each time: He should give her the appropriate beating according to Allah’s Book, but not Hurl reproaches at her. He said a fourth time: If she does it again, he should give her the appropriate beating according to Allah’s Book, and then should sell her even if only for a rope of hair.
Grade: Sahih

Hadith #4525 - Sunan Abi Dawud - Anas ibn Malik; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
I swear by Allah, Sahl had a misunderstanding about this tradition. The Messenger of Allah (ﷺ) wrote to the Jews: A slain man has been found amongnst you, so pay his bloodwit. They wrote (to him): Swearing by Allah fifty oaths, we neither killed him nor do we know his slayer. He said: Then the Messenger of Allah (ﷺ) himself paid his bloodwit which consisted of one hundred she-camels.
Grade: Da'if

Hadith #4533 - Sunan Abi Dawud - Anas ibn Malik; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
That Sa’d b. ‘Ubadah said to the Messenger of Allah (ﷺ) : What do you think if I find with my wife a man ; should I give him some time until I bring four witnesses ?” He said: “Yes”.
Grade: Sahih

Hadith #4610 - Sunan Abi Dawud - al-Nadr bin Shumayl al-Maazni النضر بن شميل المازني أبو الحسن النحوي; al-Rabi' bin Sulaiman الربيع بن سليمان; Asad bin Musa - Asad al-Sunnah أسد بن موسى بن إبراهيم - أسد السنة; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Hmad bin Dlyl حماد بن دليل; Imran bin Milhan, Abu Raja' al-Atardi عمران بن ملحان أبو رجاء العطاردي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qabaysa bin 'Uqba bin Muhammad قبيصة بن عقبة بن محمد بن سفيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Muslim who offends most against the Muslims is he who enquires about something which has not been forbidden to men, and it is declared forbidden because of his enquiry.
Grade: Sahih

Hadith #4618 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hasan came to us. The jurists of Mecca told me that I should speak to him that some day he should hold a meeting for them and preach to them. He said: Yes. So they gathered and he addressed them. I did not see anyone on orator greater than him. A man said: Abu Sa’id, who created Satan? He replied: Glory be to Allah! Is there any creator other than Allah? Allah created Satan, and he created good and created evil. The man said: May Allah ruin them! How do they lie to this old man.
Grade: Sahih

Hadith #4627 - Sunan Abi Dawud - Jami' bin Abi Rashid جامع بن أبي راشد الكاهلي; Muhammad bin 'Ali bin al-Hanfiyyah محمد بن الحنفية; Muhammad bin al-Salt al-Basri محمد بن الصلت البصري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We used to say in the times of the Prophet (ﷺ): We do not compare anyone with Abu Bakr. ’Umar came next and then ‘Uthman. We then would leave (rest of) the companions of the Prophet (ﷺ) without treating any as superior to other.
Grade: Sahih

Hadith #4631 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
The Caliphs are five: Abu Bakr, ‘Umar, ‘Uthman, ‘All and ‘Umar b. ‘Abd al-Aziz.
Grade: Da'if

Hadith #4690 - Sunan Abi Dawud - Hudhayfah ibn al-Yaman; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Muhammad bin Zayd عمر بن محمد بن زيد بن عبد الله (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man commits fornication, faith departs from him and there is something like a canvas roof over his head; and when he quits that action, faith returns to him.
Grade: Sahih

Hadith #4697 - Sunan Abi Dawud - Abdullah bin al-Dayli; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Khalid al-Hmyry Abu وهب بن خالد الحميري (Sunan Abi Dawud)
What is Islam? He replied : It means saying prayer, payment of zakat, performing HAJJ, fasting during RAMADAN, and taking a bath on account of sexual defilement. Abu Dawud said: ‘Alqamah was a Murji’i.
Grade: Sahih

Hadith #4706 - Sunan Abi Dawud - Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; ibn Mas'ud; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) explaining the verse “As for the youth his parents were people of Faith,” he was created infidel the day when he was created.
Grade: Sahih

Hadith #4711 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة (Sunan Abi Dawud)
Allah knows best about what they were doing.
Grade: Sahih

Hadith #4732 - Sunan Abi Dawud - Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Uthman bin al-Mughira al-Thqfy عثمان بن المغيرة الثقفي مولاهم أبو المغي (Sunan Abi Dawud)
Allah will fold the heavens an the day of Resurrection, then seizing them in His right hand he will say: I am the king. Where are the mighty men? Where are the proud men? He will then fold the earths and take them in his other hand (According to the version of Ibn al-Ala), and then say ; I am the King. Where are the mighty men? Where are the proud men?
Grade: Sahih

Hadith #4762 - Sunan Abi Dawud - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Sa'id al-Khudri; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
various corruptions will arise in my community, so strike with sword the one who tries to cause separation in the matter of Muslims when they are united, whoever he be.
Grade: Sahih

Hadith #4765 - Sunan Abi Dawud - Khaythama bin 'Abdur Rahman خيثمة بن عبد الرحمن بن أبي سبرة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Soon there will appear disagreement and dissension in my people; there will be people who will be good in speech and bad in work. They recite the Qur’an, but it does not pass their collar-bones. They will swerve from the religion as an animal goes through the animal shot at. They will not return to it till the arrow comes back to its notch. They are worst of the people and animals. Happy is the one who kills them and they kill him. They call to the book of Allah, but th
Grade: Sahih

Hadith #4945 - Sunan Abi Dawud - Hudhayfah ibn al-Yaman; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I swore allegiance to the Messenger of Allah (ﷺ) promising to hear and obey, and behave sincerely towards every Muslim. AbuZur’ah said: Whenever he sold and bought anything, he would say: What we took from you is dearer to us than what we gave you. So choose (as you like).
Grade: Sahih

Hadith #4984 - Sunan Abi Dawud - Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Uthman bin al-Mughira al-Thqfy عثمان بن المغيرة الثقفي مولاهم أبو المغي (Sunan Abi Dawud)
The desert Arabs may not dominate you in respect of the name of your prayer. Beware! It is al-`Isha, but they milk their camels when it is fairly dark.
Grade: Sahih

Hadith #5016 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubada bin As-Samit (Sunan Abi Dawud)
The verse “And the poets it is those straying in evil who follow them. He (Allah) then abrogated it and made an exception saying: Except those who believe and work righteousness, engage much in the remembrance of Allah.”
Grade: Hasan

Hadith #5037 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
when a man sneezed beside the prophet (May peace be upon him), he said to him : Allah have mercy on you, but when he sneezed again, he said : The man has a cold in the head.
Grade: Sahih

Hadith #5127 - Sunan Abi Dawud - Abu Mas'ud al-Badri; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Iyas, Abu 'Amr Shaybani سعد بن إياس أبو عمرو الشيباني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
I never saw the Companions of the Messenger of Allah (May peace be upon him) so happy about anything as I saw them happy about this thing. A man said : Messenger of Allah! A man loves another man for the good work which he does, but he himself cannot do like it. The Messenger of Allah (May peace be upon him) said: A man will be with those whom he loves.
Grade: Sahih

Hadith #5135 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Al-Ala b. al-Hadrami wrote to the prophet (May peace be upon him), and he began with his name.
Grade: Da'if

Hadith #5137 - Sunan Abi Dawud - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A son does not repay what he owes to his father unless he buys him and emancipates him if he finds him in slavery.
Grade: Sahih

Hadith #5193 - Sunan Abi Dawud - Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Imran bin Husain; Imran bin Milhan, Abu Raja' al-Atardi عمران بن ملحان أبو رجاء العطاردي; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
By him in whose hand my soul is, you will not enter Paradise until you believe, and you will not believe until you love one another: should I not guide you to something doing which you will love one another: spread out salutation among you.
Grade: Sahih

Hadith #5267 - Sunan Abi Dawud - Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) prohibited to kill four creatures: ants, bees, hoopoes, and sparrow-hawks.
Grade: Sahih